The Relationship Between Job Demands and Burnout in Terms of Personality Type in Employees - Afriani, Mita; Salim, Agus (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Every organisation hopes to expand and achieve its objectives, hence it demands optimal performance from each employee. An individual's performance at work will be affected by high demands. Employee productivity will decrease because of the physical and psychological issues experienced. The decrease in employee productivity and quality of work is related to various personality types, resulting in different stress management strategies for each individual. This study aims to determine the relationship between job demands and burnout regarding employee personality types. This study involved 144 employees selected by nonprobability sampling, specifically utilising incidental sampling techniques. The instruments employed included the burnout scale (α = 0.891), the job demands scale (α = 0.922), and the personality type scale (α = 0.689). The data analysis results, derived from the ANCOVA test, obtained a significance level of 0.000 (p < 0.05). The results showed a significant relationship between job demands and burnout regarding employee personality types. This research serves as evaluative material for employers to create a better work environment and reduce the occurrence of burnout. Setiap Perusahaan berharap dapat berkembang dan mencapai tujuan yang telah direncanakan, sehingga Perusahaan menginginkan performa kerja yang baik dari setiap karyawannya. Performa kerja seseorang akan dipengaruhi oleh tuntutan kerja yang tinggi. Produktivitas karyawan akan menurun dikarenakan permasalah fisik dan permasalahan psikologis yang dirasakan. Penurunan produktivitas serta kualitas kerja pada karyawan juga disebabkan karyawan memiliki tipe kepribadian yang berbeda, sehingga dalam mengelola stress pada masing-masing individu berbeda. Penelitian ini bertujuan untuk mengetahui hubungan job demands dengan burnout ditinjau dari tipe kepribadian pada karyawan. Subjek penelitian ini sebanyak 144 karyawan dengan Teknik pengambilan sampling menggunakan nonprobability sampling dengan jenis Teknik sampling yang digunakan adalah sampling insidental. Instrument yang digunakan yaitu skala burnout (a=0,891), skala job demands (a=0,922) dan skala tipe kepribadian (a=0,689). Berdasarkan hasil analisis data menggunakan uji ancova didapatkan hasil dengan taraf signifikansi sebesar 0.000 (p